The Vanadium(V) Oxoazides [VO(N3)3], [(bipy)VO(N3)3], and [VO(N3)5]2−1. (12th June 2015) - Haiges, Ralf; Vasiliu, Monica; Dixon, David A.; Christe, Karl O.
Abstract Vanadium(V) oxoazide [VO(N3)3] was prepared through a fluoride–azide exchange reaction between [VOF3] and Me3SiN3 in acetonitrile solution. When the highly impact‐ and friction‐sensitive compound [VO(N3)3] was reacted with 2, 2′‐bipyridine, the adduct [(bipy)VO(N3)3] was isolated. The reaction of [VO(N3)3] with [PPh4]N3 resulted in the formation and isolation of the salt [PPh4]2[VO(N3)5]. The adduct [(bipy)VO(N3)3] and the salt [PPh4]23[VO(N3)5] were characterized by vibrational spectroscopy and single‐crystal X‐ray structure determination, making these compounds the first structurally characterized vanadium(V) azides.